Al-'Aqlu wa al-Hikmah fi al-Qur'an al-Kareem wa al-Sunnah al-Nabawiyah - Hamad, Mohammed Abdul Razaq (International Conference on Islamic Studies, 2023)
The most honorable thing that researchers present in their research is what is in the service of the Great Qur’an and its glorious and bright sciences and the goal that it strives to achieve. Given that, I found in myself an urgent desire for his book (Wisdom and Reason in the Holy Qur’an), so it was the lost thing that I was seeking, so I decided to do this research. I seek help from the Most Gracious God, relying on Him, asking God Almighty to help me complete this effort. The research has been divided into an introduction and three sections. The first topic: Defining wisdom and reason in language and terminology. The second topic: Wisdom in the Qur’an and the Sunnah of the Prophet. The third topic: The mind. In the Qur’an and the Sunnah of the Prophet.